Effect Of Pretreatment On Eh Response Of A Gold Electrode - S. Chander (Society for Mining, Metallurgy & Exploration, 1989)
The effect of pretreatment potential on the response of a gold electrode for Eh measurements in sulfide solutions was examined in terms of measured Eh values and electrode response time. The electrode response time is defined as the time required for the electrode to reach a steady-state value. The relationship between measured Eh values and the hydrosulfide ion concentration is established. The effect of pH, the reversibility of the gold electrode in the sulfide solutions, and the reproducibility of measurements are also investigated. A mixed potential theory is proposed to explain the observations.